Implementasi Kurikulum Merdeka dan Pendidikan Karakter: Strategi Meningkatkan Kualitas Siswa di Era Modern - Nofry Vincensius Wongkar; Richard Daniel Herdi Pangkey (Departement of Mathematics Education, 2024)
As a result of the lack of character education for children, it causes a moral crisis, such as social problems in society, drinking, bullying and others. Character education in the Independent curriculum is very important because it has several main objectives. First, the character of Education aims to develop the basic character of students in accordance with the values of Pancasila, such as religious, nationalist, integrity, independence, and mutual assistance. Second, the character of education is expected to form students who have religious spiritual strength, self-control, personality, intelligence, noble character, and other skills needed to face complex future challenges. The method in this study using literature studies. Through the new policy of Education Quality reform in Indonesia curriculum “Merdeka belajar